Tax, Welfare, and Pension Reforms in Slovenia : Implications for Work Incentives and Labor Participation - Egoume Bossogo, Philippe; Tuladhar, Anita (Washington, D.C. : International Monetary Fund, 2006)
The labor participation rate in Slovenia has been lower than in the EU-15 (the members states prior to May 2004), particularly for the low-income and older individuals. Using simulations of tax and social benefits and public pensions, the paper shows how the current tax, welfare, and pension systems create disincentives to work among these groups. The paper finds that incentives to retire early are strong for men, especially low-wage earners. The marginal effective tax rates also make it costly for low-income individuals to work and negatively affect the probability of participating. The paper proposes reform measures to enhance work incentives and labor participation, which will be crucial for dealing with population aging and for achieving higher potential growth in Slovenia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet